2018
DOI: 10.1177/2331216518789551
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Possible Perceptual and Physiological Effects of Wind Turbine Noise

Abstract: This review considers the nature of the sound generated by wind turbines focusing on the low-frequency sound (LF) and infrasound (IS) to understand the usefulness of the sound measures where people work and sleep. A second focus concerns the evidence for mechanisms of physiological transduction of LF/IS or the evidence for somatic effects of LF/IS. While the current evidence does not conclusively demonstrate transduction, it does present a strong prima facia case. There are substantial outstanding questions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…In a further publication, the committee [12] recognised and responded to the need to review the scientific literature relating to possible perceptual and physiological effects of infrasound and low-frequency sound (IS/LF). Previous reviews [13][14][15][16][17][18][19][20][21] have mostly relied on an epidemiological approach providing meta-analysis of the existing populationbased research.…”
Section: Possible Perceptual and Physiological Effects Of Wind Turbinmentioning
confidence: 99%
See 4 more Smart Citations
“…In a further publication, the committee [12] recognised and responded to the need to review the scientific literature relating to possible perceptual and physiological effects of infrasound and low-frequency sound (IS/LF). Previous reviews [13][14][15][16][17][18][19][20][21] have mostly relied on an epidemiological approach providing meta-analysis of the existing populationbased research.…”
Section: Possible Perceptual and Physiological Effects Of Wind Turbinmentioning
confidence: 99%
“…Studies of the generation and propagation of IS/LF sound by wind turbines demonstrate that the acoustical energy per unit frequency at the blade-passing frequency (BPF) and at its harmonic frequencies below 10-15 Hz is greater than at higher frequencies. Propagation models and field studies have indicated that sound at these IS/LF frequencies can propagate with less attenuation with distance than higher frequencies because of their lower sound absorption during passage through the air and on reflection from the ground [12,[22][23][24][25][26][27][28]. Added to this is uncertainty regarding the effectiveness of sound insulation of houses at infrasound and low frequencies [29].…”
Section: Possible Perceptual and Physiological Effects Of Wind Turbinmentioning
confidence: 99%
See 3 more Smart Citations